Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

not native English speaker so I may get some terms wrong and so on.

On to the question:

I have as an assignment to find a polynomial function $f(x)$ with the coefficients $a$, $b$ and $c$ (which are all integers) which has one root at $x = \sqrt{a} + \sqrt{b} + \sqrt{c}$.

I've done this with $f(x) = 0$ where $x = \sqrt{a} + \sqrt{b}$ through an iterative method which looks like this (forgive me for my pseudo code):

  1. var x = sqrt(a) + sqrt(b)
  2. Set x to x multiplied by the conjugate of x
  3. Repeat from step 2 until all square roots are gone

The full calculation looks like this (the exponent signs disappeared, sorry about that):

$(x-(\sqrt{a}+\sqrt{b}))(x+(\sqrt{a}+\sqrt{b})) = x^2-(\sqrt{a} +\sqrt{b})^2 \\ = x^2-(a+2\sqrt{a}\sqrt{b} +b) \\ = x^2-a-b-2\sqrt{a}\sqrt{b} $

$((x^2-a-b)-(2\sqrt{a}\sqrt{b} ))(( x^2-a-b)+(2\sqrt{a}\sqrt{b} )) = x^4-2ax^2-2bx^2+2ab+a^2+b^2-4ab \\ = x^4-2ax^2-2bx^2-2ab+a^2+b^2 \\ = x^4-2x^2(a+b)-2ab+a^2+b^2$

$p(x) = x^4-2x^2(a+b)-2ab+a^2+b^2$

And then I used the factor theorem to calculate the remaining roots, which gave the following results: $x = (\sqrt{a} +\sqrt{b} )$, $x = -(\sqrt{a} +\sqrt{b} )$, $x = (\sqrt{a} -\sqrt{b} )$ and $x = -(\sqrt{a} - \sqrt{b})$.

When I try the same method on $x = \sqrt{a} + \sqrt{b} + \sqrt{c}$, the calculations just become absurd. Any kind of help would be enormously appreciated!

share|improve this question

2 Answers 2

Subtract $\sqrt a$ from both sides, square both sides: now you have $\sqrt a$ on one side, $\sqrt{bc}$ on the other. Solve for $\sqrt a$, square both sides: now you have only $\sqrt{bc}$. Solve for $\sqrt{bc}$, square both sides, voila! all square roots gone.

If you need to know the other zeros, the full set is $\pm\sqrt a\pm\sqrt b\pm\sqrt c$ where the signs are to be taken independently of each other (making 8 zeros in all).

share|improve this answer

You certainly have the right idea. Following Gerry Myerson's suggestion above, we have \begin{align} x&=\sqrt{a}+\sqrt{b}+\sqrt{c}\\ x-\sqrt{a}&=\sqrt{b}+\sqrt{c}\\ (x-\sqrt{a})^2=x^2-2x\sqrt{a}+a&=b+2\sqrt{bc}+c=(\sqrt{b}+\sqrt{c})^2\\ x^2+a-b-c&=2x\sqrt{a}+2\sqrt{bc}\\ \left(x^2+a-b-c\right)^2&=4x^2a+8x\sqrt{abc}+4bc\\ \left(x^2-a+b+c\right)^2-4x^2a-4bc&=8x\sqrt{abc}\\ \left(\left(x^2-a+b+c\right)^2-4x^2a-4bc\right)^2&=64abc\cdot x^2. \end{align} Expanding this will yield a polynomial with integer coefficients (assuming $a$, $b$, and $c$ are integers) which has a zero at $x=\sqrt{a}+\sqrt{b}+\sqrt{c}$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.